Social Interpretation of Sulang Silima in the Empowerment of the Zam-Zam Pond Mosque in Dairi Regency, North Sumatera - Sahrul, Sahrul; Daulai, Afrahul Fadhila (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This This research aims to describe the role of Sulang Silima local wisdom; perisang-isang, pertulan Tengah, perukur-ukur, puhun and anak berru in empowering the Telaga Zam Zam mosque in Dairi Regency, North Sumatra. The type of research is qualitative, the data collection tools used are observation and interviews with religious and traditional leaders who know exactly the Sulang Silima culture. Based on the research results, it was found that the local wisdom of Sulang Silima can be interpreted socially in empowering the Telaga Zam Zam mosque. Perisang-isang is synonymous with the protective and advisory section of the Mosque Prosperity Board (BKM). The middle person is the Chairman of the Mosque Prosperity Board, secretary and treasurer. Perukur-ukur are areas or sections of mosque management; da'wah, education, social welfare and public relations.  Puhun is synonymous with the field of mosque planning and programming. Meanwhile, Berru's children are mosque marbots; janitors, muezzins and mosque guards. These five elements are collaborative and complement each other in carrying out their respective duties and functions. In practice, these five elements of local culture were transferred into Islamic acculturation and turned out to be effective in empowering the Telaga Zam Zam mosque.